Editorial - Gautam, Ganga Ram (Janabhawana Research Journal, 2024)
Research Management Cell (RMC), Jana Bhawana Campus, has put an effort to shape this issue through the amalgamation of diverse perspectives and expertise of authors. It consists of 12 articles from authors with diverse academic backgrounds and inclusivity. These articles have not only broadened the scope of research but also provided voices from various strata of life. The first article "Impact of Financial Risk and Macro-Economic Variable on Stock Return: Evidence from Commercial Banks of Nepal" examines the impact of financial risks and macroeconomic variables on the stock returns of commercial banks in Nepal. The other article "Comparison of Job Satisfaction of Private and Public School Teachers in Godawari Municipality" claims that the teachers of private schools were more satisfied in comparison to public schools in terms of working environment, staff relationship, and motivation; and there was no difference in the satisfaction between the private and public-school teachers. The next article "A Pilot Study Approach to Assessing the Reliability and Validity of Relevancy and Efficacy Survey Scale" assesses the reliability and validity of the attitude measurement scale towards the relevance of mathematical knowledge of real analysis for secondary-level mathematics instruction. Likewise, the article "Motivating Factors to the Success of Youth Enterprise Startups: A Study of Nepali Enterprises" concludes that entrepreneurial exposure, training, and education are the significant factors impacting the motivation of youth entrepreneurship startups. The article entitled "Effect of International Trade on Economic Growth of Nepal" emphasizes that the Government should ensure export promotion policies to achieve Nepal's high and sustainable economic growth by investing in trade infrastructure and export subsidies. It urges for creating a favorable environment that encourages using remittance money to support productive sectors of the economy. Similarly, the article "Comparison of Academic Performances of Students among Various Ethnic Groups in Godawari Municipality" compares differences in academic performances of students among various ethnic groups (Brahmin/Chhetri vs non-Brahmin/Chhetri) and gender (male vs female). Further, the article "Soft Adventure and Spiritual Tourism: A Case Study of Khaptad National Park" explores the elements of adventure tourism in the Khaptad area and concludes that the land can be the milestone of Nepalese soft adventure sports tourism including spiritual, cultural, and eco-tourism. The other article, "Reshaping Multiculturalism through Accommodation, Encouragement and Respect: An Analytical Study of Zadie Smith's White Teeth" concludes that accommodation rather than assimilation, encouragement rather than mere tolerance of difference or a form of white paternalism, and respect for others in their terms are some of the ways to reshape multiculturalism. In addition, the article "Continuation of Learning During COVID-19 Situation in Nepal" explores the obstacles and ways of continuation for learning faced by school teachers during the COVID-19 pandemic. Another article "Perceptions of Secondary Level English Teachers on In-Service Teacher Training: A Narrative Inquiry", focuses on the need for ICT-based teacher training rather than theory-laden conventional training and claims that the teachers were not satisfied with the top-down approach of in-service teachers training packages. In the same way, the article, "The Resilience of Post-Trafficked Women: A Narrative Inquiry" concludes that comprehensive support systems, policy reforms, and innovative solutions are essential to enhance the resilience and recovery of trafficking survivors. The last article "Patterns of Internet Use by the Teachers: An Inquiry of School Students of Nagarjun Municipality" attempts to identify the patterns of teenage students towards the use of internet. The editorial team extends its gratitude to all the reviewers, authors, and other personnel who have contributed to this issue.